2012
DOI: 10.1063/1.4709392
|View full text |Cite
|
Sign up to set email alerts
|

Reversible high-pressure phase transition in LaN

Abstract: In situ high-pressure X-ray powder diffraction experiments on LaN up to 60.1 GPa at ambient temperature in a diamond-anvil cell revealed a reversible, first-order structural phase transition starting at $22.8 GPa and completed at $26.5 GPa from the ambient cubic phase (Fm 3m, no. 225) to a tetragonal high-pressure phase (P4/nmm, no. 19, a ¼ 4.1060(6), c ¼ 3.0446(6) Å , Z ¼ 2, wR p ¼ 0.011), which has not been claimed in theoretical predictions. HP-LaN is isotypic with a high-pressure polymorph of BaO, which cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
37
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 37 publications
(54 reference statements)
11
37
1
Order By: Relevance
“…Additionally, we predict that upon further compression the B10 phase will transform to B2 structure at $165 GPa. Additionally, in ratio and internal parameter z along with the available experimental data 15 for LaN. Our theoretical c/a ratio and z parameter agree with experimental data within $8% and $2.8%, respectively, demonstrating that the theoretical calculations correctly reproduce the experimental data of LaN, 15 thereby supporting our findings on CeN.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…Additionally, we predict that upon further compression the B10 phase will transform to B2 structure at $165 GPa. Additionally, in ratio and internal parameter z along with the available experimental data 15 for LaN. Our theoretical c/a ratio and z parameter agree with experimental data within $8% and $2.8%, respectively, demonstrating that the theoretical calculations correctly reproduce the experimental data of LaN, 15 thereby supporting our findings on CeN.…”
Section: Resultssupporting
confidence: 78%
“…Finally to test whether the calculations carried out using present theoretical method can reproduce the experimental observations of Schneider et al 15 on statically compressed LaN, we have carried out total energy calculations on B1, B10, and B2 structures of these materials also. The theoretically determined enthalpy is compared for these three phases at various pressures in LaN (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The direction of the shift is reversed for the neighboring Ln. Shortly following the PrN result, Schneider et al reported the same type of transition for LaN, 16 and the transition has since been rationalized in terms of a Peierls distortion. 17 Shortly before the publication of the LaN result by Schneider et al, a paper reporting experimental evidence for a (partial) B1 to B2 transition in CeN, using energy dispersive powder X-ray diffraction (ED-PXRD), was published by Staun Olsen et al 18 This result was also backed up by theoretical calculations.…”
Section: Introductionmentioning
confidence: 93%